2021
DOI: 10.1002/ett.4355
|View full text |Cite
|
Sign up to set email alerts
|

A fully distributed energy‐aware multi‐level clustering and routing for WSN‐based IoT

Abstract: One of the major problems in wireless sensor networks (WSNs) is that resource-constrained sensor nodes consume their limited batteries quickly due to long-distance data communications. The communication distance of the nodes can be decreased using clustering architectures and multi-hop data transmissions; hence, the lifetime of the network can be increased. In this study, two-level intra-cluster and multi-level inter-cluster communication are proposed. The coverage area of the second-level clusters is dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…1 and Fig. 3 offer a comparative energy consumption (ECN) assessment of the IRSO-EAMHR model with recent models such as fully distributed energy aware multi-level clustering and routing (FDE), Energy-Efficient Optimal Multi-path Routing Protocol (EEOMPRP), Wolf optimization for multi-path routing protocol (WOMPR), CoAP congestion control for the internet of things (CoAP-IOT), and Collision-Aware Routing Using Multi-Objective Seagull Optimization Algorithm (CAR-MOSOA)under distinct nodes [18][19][20][21][22]. The results indicated that the IRSO-EAMHR model has resulted in effectual outcome with lower ECN over the other algorithms under distinct count of nodes.…”
Section: Experimental Analysismentioning
confidence: 99%
“…1 and Fig. 3 offer a comparative energy consumption (ECN) assessment of the IRSO-EAMHR model with recent models such as fully distributed energy aware multi-level clustering and routing (FDE), Energy-Efficient Optimal Multi-path Routing Protocol (EEOMPRP), Wolf optimization for multi-path routing protocol (WOMPR), CoAP congestion control for the internet of things (CoAP-IOT), and Collision-Aware Routing Using Multi-Objective Seagull Optimization Algorithm (CAR-MOSOA)under distinct nodes [18][19][20][21][22]. The results indicated that the IRSO-EAMHR model has resulted in effectual outcome with lower ECN over the other algorithms under distinct count of nodes.…”
Section: Experimental Analysismentioning
confidence: 99%
“…Increasing the efficiency and scalability are the most important benefits of distributed algorithms. The ideas proposed in References 12,15,25,26,28,29,36,41,[54][55][56][57][58][59][60] are formed based on distributed clustering algorithm. Also, ideas proposed in References 13,14 are formed based on centralized clustering algorithm.…”
Section: Clustering Approachesmentioning
confidence: 99%
“…Abasıkeleş‐Turgut and Altan 28 proposed a fully distributed energy‐aware multi‐level clustering and routing (FDEAM) approach to overcome the drawback associated with resource‐constrained sensor nodes in long‐distance communication. The communication distance that exists between the nodes is minimized via the multi‐level inter‐cluster and two‐level intracluster communications.…”
Section: Literature Surveymentioning
confidence: 99%